A study on the application of nicenet for learning - Kang, Sian Lee (2002)
The aim of this research is to investigate how KUiTTHO students use an online forum in the process of learning; how KUiTTHO students communicate with their lecturer and the socio-linguistic aspect of using and online platform. The participants of this research were students from Electrical Department who were taking the subject- Electric and Magnet subject in KUiTTHO. The number of the students in the sample class was 63. This research is a combination of qualitative and quantitative methods. The researcher used four methods in the data collection. They were interview, observation, content analysis and questionnaire. The online platform used to conduct this research was Nicenet. At the end of this research, the finding suggests that online classroom should be applied into the process of teaching and learning in institution of higher education in Malaysia such as KUiTTHO